2016
DOI: 10.1371/journal.pone.0159372
|View full text |Cite
|
Sign up to set email alerts
|

Antennal and Abdominal Transcriptomes Reveal Chemosensory Genes in the Asian Citrus Psyllid, Diaphorina citri

Abstract: The Asian citrus psyllid, Diaphorina citri is the principal vector of the highly destructive citrus disease called Huanglongbing (HLB) or citrus greening, which is a major threat to citrus cultivation worldwide. More effective pest control strategies against this pest entail the identification of potential chemosensory proteins that could be used in the development of attractants or repellents. However, the molecular basis of olfaction in the Asian citrus psyllid is not completely understood. Therefore, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 97 publications
2
47
0
Order By: Relevance
“…In insects, the characterization of metabolizing enzymes received an increasing interest with regard to their role in insecticide resistance, adaptation to host plant volatile and their function; as ODEs, in the termination of the olfactory signal to maintain a relatively high olfactory sensitivity toward new stimuli. In particular, recent studies investigating the antennal transcriptome in different species identified varied ODEs including CYP, CES, GST and UGT [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These reports have completed and confirmed the case-by-case identification of previously characterized ODEs [25][26][27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 59%
“…In insects, the characterization of metabolizing enzymes received an increasing interest with regard to their role in insecticide resistance, adaptation to host plant volatile and their function; as ODEs, in the termination of the olfactory signal to maintain a relatively high olfactory sensitivity toward new stimuli. In particular, recent studies investigating the antennal transcriptome in different species identified varied ODEs including CYP, CES, GST and UGT [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These reports have completed and confirmed the case-by-case identification of previously characterized ODEs [25][26][27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 59%
“…CSPs may therefore be expressed in multiple tissues where they regulate a variety of processes in insects often, but not always, upon binding small molecules. Aphids have about 10 CSP genes, and similar numbers were identified in related plant-sucking insects of the order Hemiptera, such as the whitefly Bemisia tabaci and psyllid Diaphorina citri (13)(14)(15)(16). Aphid CSPs were previously known as OS-D-like proteins (17).…”
Section: Introductionmentioning
confidence: 96%
“…The discovery that all of the annotated CSPs in Daphnia pulex , an aquatic crustacean that is evolutionarily distant to insects, are pentahelical suggests that the pentahelical CSP clade pre‐dates terrestrial colonization and has thus likely gained new functionalities in development and cellular homeostasis. The presence of two different genes encoding these CSPs in L. lineolaris and L. hesperus along with T. castaneum (Vieira & Rozas, ), A. mellifera (Wanner et al ., ; Forêt et al ., ; Vieira & Rozas, ), A. pisum (Vieira & Rozas, ), Anopheles gambiae (Vieira & Rozas, ), and Diaphorina citri (Wu et al ., ) suggests that the lone genes reported in D. melanogaster (Vieira & Rozas, ) and Pediculus humanus (Vieira & Rozas, ) may be the result of gene loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although CSPs have been most extensively characterized in dipterans and lepidopterans, advances in transcriptomic resources have facilitated their identification in a number of hemipterans (Jacobs et al ., ; Zhou et al ., , , , ; Xu et al ., ; Gu et al ., , ; Hua et al ., , ; Futahashi et al ., ; Ribeiro et al ., ; Sun et al ., ; Cui et al ., ; Wang et al ., ; Wu et al ., ; Xue et al ., ; Liu et al ., ). Similar to CSPs in other insect orders, hemipteran CSPs are broadly expressed (Zhou et al ., , , ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%